2009
DOI: 10.1186/1745-6215-10-52
|View full text |Cite
|
Sign up to set email alerts
|

A review of reporting of participant recruitment and retention in RCTs in six major journals

Abstract: Background: Poor recruitment and retention of participants in randomised controlled trials (RCTs) is problematic but common. Clear and detailed reporting of participant flow is essential to assess the generalisability and comparability of RCTs. Despite improved reporting since the implementation of the CONSORT statement, important problems remain. This paper aims: (i) to update and extend previous reviews evaluating reporting of participant recruitment and retention in RCTs; (ii) to quantify the level of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 21 publications
5
159
3
2
Order By: Relevance
“…have looked at how often reports of RCTs include quantitative data for the recruitment process (5)(6)(7)(8). One of the comprehensive reviews of these investigated the recruitment process in 172 reports of RCTs published in 4 highimpact medical journals between 1999 and 2000.…”
Section: Simsek and Yazicimentioning
confidence: 99%
See 1 more Smart Citation
“…have looked at how often reports of RCTs include quantitative data for the recruitment process (5)(6)(7)(8). One of the comprehensive reviews of these investigated the recruitment process in 172 reports of RCTs published in 4 highimpact medical journals between 1999 and 2000.…”
Section: Simsek and Yazicimentioning
confidence: 99%
“…We also analyze the association between recruitment rates and trial characteristics. A number of publications have studied the reporting process of RCTs in various subspecialties of medicine (5)(6)(7)(8). However, no study, to the best of our knowledge, has investigated RCTs focusing on RA alone to date.…”
Section: Introductionmentioning
confidence: 99%
“…8,[14][15][16][17][18] While some stages were well reported, others were depicted incompletely. In cases of trials published in major journals, 85-90% reported the enrollment fraction, whereas only 40-60% reported the eligibility fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Učestalost dijagrama toka je obrađena u okviru sistematskog pregleda randomizovanih kontrolnih studija o toku ispitanika [9]. Autori ovog istraživanja beleže učestalost grafičkog prikaza toka studije u 2/3 izveštaja što pokazuju i naši rezultati kada su u pitanju ogledi sa klaster randomizacijom.…”
Section: Diskusijaunclassified